Develop and test a method to convert wired systems into wireless systems ( wireless communication) - Habib, Farhana; Drong, Anne (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2011.